2019
DOI: 10.1002/ese3.351
|View full text |Cite
|
Sign up to set email alerts
|

A novel numerical model of gas transport in multiscale shale gas reservoirs with considering surface diffusion and Langmuir slip conditions

Abstract: Multiflow mechanisms coexist in shale gas reservoirs (SGRs) due to the abundant nanopores and the organic matter as a medium of gas souring and storage. The gas transport mechanisms in nanopores including bulk gas transfer and adsorption‐gas surface diffusion were already investigated in pore‐scale models, but their effects on actual gas production of multistage fractured horizontal wells in SGRs are not clearly understood, which are crucial for the economic development of unconventional resources. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…In addition to adsorption/desorption and dissolution, the discrepancy between transport capacity of isotopic gases during transport through shale pores also results in isotope fractionation. Multiple flow mechanisms (e.g., viscous flow, slip flow, Knudsen diffusion, and surface diffusion) coexist in shale reservoirs because of the multiscale flow paths [micropores (<2 nm), mesopores (2–50 nm), and macropores (>50 nm)] and the complex pore structures in them. In the early stage of shale gas production, the pressure in pores is high and viscous flow is dominant . The mean free path of methane isotopes is small (i.e., intermolecular collision is dominant), and the isotope fractionation is not obvious .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition to adsorption/desorption and dissolution, the discrepancy between transport capacity of isotopic gases during transport through shale pores also results in isotope fractionation. Multiple flow mechanisms (e.g., viscous flow, slip flow, Knudsen diffusion, and surface diffusion) coexist in shale reservoirs because of the multiscale flow paths [micropores (<2 nm), mesopores (2–50 nm), and macropores (>50 nm)] and the complex pore structures in them. In the early stage of shale gas production, the pressure in pores is high and viscous flow is dominant . The mean free path of methane isotopes is small (i.e., intermolecular collision is dominant), and the isotope fractionation is not obvious .…”
Section: Introductionmentioning
confidence: 97%
“…22−25 In the early stage of shale gas production, the pressure in pores is high and viscous flow is dominant. 26 The mean free path of methane isotopes is small (i.e., intermolecular collision is dominant), and the isotope fractionation is not obvious. 4 The mean free path of methane isotopes increases during the pressure depletion process, and Knudsen diffusion dominates when the pressure in shale nanopores is low.…”
Section: Introductionmentioning
confidence: 99%
“…Shale gas reservoirs have pore structures distinct from conventional gas reservoirs. The pores in organic matter are important storage spaces for shale reservoirs and contribute significantly to reservoir production. , Research has shown that the main contributors to shale gas productionincluding in the Barnett, Marcellus, and Haynesville reservoirsare from organic pores. , The pore radius of organic matter ranges from 5 nm to 800 nm, most of which are distributed over 100 nm, and the pore throat diameter is generally between 10 and 20 nm. The nanopores existing in shale reservoirs have large internal surface areas, and the ratio of adsorbed gas to total gas may exceed 50% . Also, it is generally believed that the high internal surface area gives the surfaces of inorganic matter, such as clay minerals in shale reservoirs, a certain adsorption capacity similar to that of organic matter surfaces. Therefore, in anhydrous reservoirs, considerable quantities of adsorbed gas exist in both organic and inorganic matter.…”
Section: Introductionmentioning
confidence: 99%
“…Song et al computed the absolute permeability of micro‐CT images by including the image voxel‐based solver, pore network model, LBM, Kozeny‐Carman equation, and Thomeer relation. Huang et al established a comprehensive apparent permeability model which couples the surface diffusion of adsorbed gas, slippage flow considering the additional flux generated by surface diffusion based on Langmuir's theory, and Knudsen diffusion. The model is validated with the experimental data and LBM simulations.…”
Section: Introductionmentioning
confidence: 99%